Antara Logika, Etika, dan Estetika dalam Pendidikan Agama Islam - Shohibul Kafi, Muhammad; Rizal Ma'arif, Muhammad; Setiawan, Eko (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2022)
Balance in education is very important, which includes logic, ethics and aesthetics. This study discusses theimportance of logic, ethics and aesthetics in Islamic religious education. Logic serves as the main source inseeking knowledge, both about the world and the hereafter. With the power of logic and the human mind will beable to find the true truth. In order to strengthen logic, a branch of Kalam was formed. The role of ethics inIslamic religious education is as the main pillar of the search for knowledge and in practicing that knowledge.This is confirmed by the main purpose of sending the Prophet Muhammad is to give a good determination aboutmorals and ethics. While the main supporting factor in Islamic religious education is the emergence of aesthetics(art) in the educational process. This aesthetic is used as an intermediary to achieve the core goals of Islamicreligious education, and the existence of aesthetics is expected to provide a different color and style in education,as has been done by most members of the Wali Songo. The conclusion of this study is that it is important to havecontinuity between logic, ethics and aesthetics in Islamic religious education.